Equilibrium configurations of systems of neutrons with allowance for nuclear and gravitational interactions; Soviet Physics Journal; Vol. 19, iss. 11 - Reizlin (Reyzlin) V. I. Valery Izrailevich (1976, 1976)
Title screen